TCP Performance Analysis in Dynamic GPRS LA - Othman, A.K.; Zakaria, M.; Khairuddin, Ab Hamid (IEEE, 2008)
This paper presents the findings on TCP performance measurements in the LA process during the deployment of GPRS CS1 and CS2 coding schemes and after the activation of two more coding schemes, CS3 and CS4. The measurements are done under various network scenarios based on users’ physical locations in one of Malaysia’s commercially deployed live GPRS networks. End-to-end evaluation of FTP application is used for the assessment together with tracing at the GPRS air interface. The results show that TCP works well in the LA process and can cope with the frequent switching between the coding schemes without any problem. Throughput performance is observed to be stable in all scenarios. The activation of higher coding schemes aided by TCP tuning also proves to be beneficial by the 23% increase in average throughput seen for urban areas.